2012
DOI: 10.3851/imp2318
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Vitamin D Deficiency and Relationship with Cardiac Biomarkers, Inflammation and Immune Restoration in HIV-Infected Youth

Abstract: Background Vitamin D deficiency is common in HIV-infected individuals. In adults, traditional and HIV-related factors play a role in vitamin D status, and deficiency appears to impair immune restoration and exacerbate HIV complications, like cardiovascular disease (CVD). This study sought to determine factors contributing to vitamin D status in HIV-infected youth and investigate the relationship with CVD risk, inflammation, and immune restoration. Methods HIV-infected subjects (1–25 years old) were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 53 publications
1
22
1
Order By: Relevance
“…Subjects receiving tenofovir did not differ at baseline or in the change in 25 In a few studies evaluating children and young adults with HIV infection, researchers found a high prevalence of suboptimal 25(OH)D, ranging from 71% to 89% <30 ng/mL [3,[26][27][28]] to 33% to 78% <20 ng/mL [1,4,[29][30][31], with 1 group reporting 87% <15 ng/mL [2]. Our results support the finding that suboptimal 25(OH)D status is common in unsupplemented youth, with 95% at baseline having a 25(OH)D <32 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects receiving tenofovir did not differ at baseline or in the change in 25 In a few studies evaluating children and young adults with HIV infection, researchers found a high prevalence of suboptimal 25(OH)D, ranging from 71% to 89% <30 ng/mL [3,[26][27][28]] to 33% to 78% <20 ng/mL [1,4,[29][30][31], with 1 group reporting 87% <15 ng/mL [2]. Our results support the finding that suboptimal 25(OH)D status is common in unsupplemented youth, with 95% at baseline having a 25(OH)D <32 ng/mL.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] We and others have demonstrated > 90% of subjects with HIV have concentrations < 30 ng/ml, which has been suggested to be optimal for vitamin D status. 2,[4][5][6] While the causes of vitamin D deficiency in HIV are multifactorial, including inadequate diet and darker skin pigmentation, certain commonly prescribed antiretroviral medications, particularly efavirenz, have been shown to interfere with normal vitamin D metabolism. 2,4,5 Vitamin D is a steroid hormone that has long been known to play a critical role in the immune system, including effects on innate immunity, adaptive immunity, and levels of inflammatory cytokines, including interleukin-6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6] While the causes of vitamin D deficiency in HIV are multifactorial, including inadequate diet and darker skin pigmentation, certain commonly prescribed antiretroviral medications, particularly efavirenz, have been shown to interfere with normal vitamin D metabolism. 2,4,5 Vitamin D is a steroid hormone that has long been known to play a critical role in the immune system, including effects on innate immunity, adaptive immunity, and levels of inflammatory cytokines, including interleukin-6 (IL-6). [7][8][9][10] In non-HIV populations, an individual's vitamin D status affects their susceptibility to tuberculosis, the disease severity, and their response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…These data are consistent with vitamin D deficiency prevalence from recent National Health and Nutrition Examination Survey (NHANES) data 12 and from studies evaluating other nonpregnant HIV-infected populations. [1][2][3] Another NHANES study demonstrated no overall statistical difference between rates of deficiency between pregnant and nonpregnant women. 13 While the rates are higher in this study compared to some studies of pregnant women, they are consistent with others, depending on the population studied.…”
mentioning
confidence: 99%
“…[1][2][3] Low vitamin D status appears to negatively affect HIV progression and mortality in nonpregnant populations. 4 Similarly, vitamin D deficiency has not only been shown to contribute to HIV disease progression and mortality in HIVinfected pregnant women in resource-limited settings, but also increases the overall risk of mother-to-child transmission (MTCT) by 46%.…”
mentioning
confidence: 99%